Transformasi Nilai Budaya Lokal dalam Membangun Akuntabilitas Organisasi Sektor Publik - Fransiskus Randa; Fransiskus E. Daromes (Jurnal Akuntansi Multiparadigma, 2014)
This study aims to transform the value of local culture of accountability to improve the implementation of the local government and public accountability. This research was conducted in the area of Tana Toraja using acculturated critical ethnography as paradigm and research method. The results show masukan (program construction activity doing by public government as agent) and keluaran accountability (public activity as principal). Reconstruction of masukan and keluaran accountability expressed in Kombongan activity (sitting together to solve the problem).